Higher Sex‐Reversal Rate of Urban Frogs in a Common‐Garden Experiment Suggests Adaptive Microevolution - Veronika Bókony; Emese Balogh; Zsanett Mikó; Andrea Kásler; Zoltán Örkényi; Nikolett Ujhegyi (Evolutionary Applications)
ABSTRACT Ectothermic vertebrates with genotypic sex determination may adjust their sexual phenotype to early‐life environmental conditions by sex reversal, and theoretical models predict diverse consequences for population dynamics and microevolution under environmental change. Environments that frequently expose individuals to sex‐reversing effects may select for or against the propensity to undergo sex reversal, depending on the relative fitness of sex‐reversed individuals. Yet, empirical data on the adaptive value and evolutionary potential of sex reversal is scarce. Here we conducted a common‐garden experiment with agile frogs (Rana dalmatina) that respond to larval heat stress by sex reversal, to test whether sex‐reversal propensity has changed via microevolution in populations that live in anthropogenic habitats where potentially sex‐reversing heat events are more frequent, compared to populations that live in cooler woodland habitats. Furthermore, to infer the adaptive value of sex reversal, we compared fitness‐related traits between heat‐exposed genotypic females that phenotypically developed into males (sex‐reversed) or females (sex‐concordant). We found that the frequency of sex reversal varied between sibgroups and was higher in the sibgroups originating from anthropogenic habitats, regardless of the thermal environment they had been exposed to during the larval sex‐determination period. Among heat‐exposed animals, time to metamorphosis was similar between sex‐reversed individuals and sex‐concordant females, but the former reached larger body mass by the end of the experiment than the latter, approaching the mass of sex‐concordant males. These results suggest that sex‐reversal propensity may have increased in anthropogenic environments by adaptive microevolution, potentially to minimize the fitness cost of reduced growth caused by heat events. Thus, environmental sex reversal has the potential to provide an adaptive strategy for ectothermic vertebrates to cope with challenges of the Anthropocene. Such knowledge on the causes and consequences of sex reversal will help pinpoint which populations are most threatened by extinction due to climatically influenced sex determination.